Low coverage of hepatitis B vaccine and determinants among health professionals working in Amhara regional state hospitals, Ethiopia - Berhanu Elfu Feleke (AOSIS, 2016)
More than two billion people have been infected with hepatitis B virus (HBV), 360 million have chronic infection and 600,000 die each year from HBV-related liver disease or hepatocellular carcinoma. Each year more than 66,000 health professionals are infected by hepatitis b virus and vaccination against hepatitis B saves the life's of these health professionals. The aim of this study was to determine the prevalence and associated factors of hepatitis B vaccine coverage in a resource limited settings. A cross sectional study design was conducted. The study was conducted on 1184 health professionals at Amhara national regional state, Ethiopia. Simple random sampling technique was used. Structured questionnaire was used to collect the data. Descriptive statistics were used to identify the prevalence while Binary logistic regression was used to assess the determinants of hepatitis B vaccine coverage. The coverage of hepatitis B vaccine was 4%. Vaccination were affected by work load (AOR=0.19, 95%CI= 0.08-0.46; P<0.01), negligence (AOR=0.04, 95%CI=0.01- 0.11: P<0.01), universal precaution training (AOR=14.75, 95%CI=5.66-38.44: P<0.01), perception that they are not at risk of infection (AOR=0.34, 95%CI=0.15-0.79: P=0.01), unaffordable cost (AOR=0.12, 95%CI=0.05-0.28: P<0.01), awareness about the vaccine (AOR=4.55, 95%CI=1.53-13.49: P<0.01), peer pressure (AOR=3.8, 95%CI=1.34-10.74: P=0.01), knowledge about where to get the vaccine (AOR=5.13, 95%CI=1.87-14.11: P=0.02), unavailability of the vaccine (AOR=0.25, 95%CI=0.1-0.63: P=0.03), year of experience (AOR=7.27, 95%CI=2.23-23.72: P<0.01). Low hepatitis B vaccine coverage was observed. The ministry of health should avail the vaccine to all those health professionals, develop awareness on HBV and improve the affordability of the vaccine.